A distinct innate lymphoid cell population regulates tumor-associated T cells - Crome, Sarah Q; Nguyen, Linh T; Lopez-Verges, Sandra; Yang, S Y Cindy; Martin, Bernard; Yam, Jennifer Y; Johnson, Dylan J; Nie, Jessica; Pniak, Michael; Yen, Pei Hua; Milea, Anca; Sowamber, Ramlogan; et al. (Nature medicine, 2017)
A previously uncharacterized population of innate lymphoid cells (ILCs) in the tumor microenvironment limits T cell expansion and cytokine production, and associates with early recurrence in patients with cancer. Depletion of this regulatory immunosuppressive cell population overcomes this effect, suggesting important implications for cancer immunotherapy. Antitumor T cells are subject to multiple mechanisms of negative regulation 1 , 2 , 3 . Recent findings that innate lymphoid cells (ILCs) regulate adaptive T cell responses 4 , 5 , 6 led us to examine the regulatory potential of ILCs in the context of cancer. We identified a unique ILC population that inhibits tumor-infiltrating lymphocytes (TILs) from high-grade serous tumors, defined their suppressive capacity in vitro , and performed a comprehensive analysis of their phenotype. Notably, the presence of this CD56 + CD3 − population in TIL cultures was associated with reduced T cell numbers, and further functional studies demonstrated that this population suppressed TIL expansion and altered TIL cytokine production. Transcriptome analysis and phenotypic characterization determined that regulatory CD56 + CD3 − cells exhibit low cytotoxic activity, produce IL-22, and have an expression profile that overlaps with those of natural killer (NK) cells and other ILCs. NKp46 was highly expressed by these cells, and addition of anti-NKp46 antibodies to TIL cultures abrogated the ability of these regulatory ILCs to suppress T cell expansion. Notably, the presence of these regulatory ILCs in TIL cultures corresponded with a striking reduction in the time to disease recurrence. These studies demonstrate that a previously uncharacterized ILC population regulates the activity and expansion of tumor-associated T cells.